Testowanie gatunku, testowanie gatunkiem - Korwin-Piotrowska, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The article refers to current genological problems in literary studies. When the author talks about ‘testing a genre’, she has in mind literary and theoretical trails of old and new literary forms. When she talks about ‘testing with a genre’, she means attempts to look at contemporary culture and its changes through the prism of a genre. The discussed issues include, among others, anamorphism of genological terms, the phenomenon of genre irony, inadequacy of old classification and ways of conducting research in the richness and distinctness of contemporary phenomena, necessity of taking into account comprehensive changes occurring in culture and cyberspace in the genological reflection.
Testing a Genre, Testing with a Genre
Keywords: literary genres; anamorphic terms; contemporary literature; gatunek literacki; terminy anamorficzne; literatura współczesna